2022
DOI: 10.3389/fmicb.2022.888645
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Biocontrol Potential of the Crude Lipopeptide by Streptomyces bikiniensis HD-087 Against Magnaporthe oryzae

Abstract: Rice blast caused by Magnaporthe oryzae is one of the most destructive plant diseases. The secondary metabolites of Streptomyces have potential as biological control agents against M. oryzae. However, no commercial secondary antimicrobial products of Streptomyces have been found by gene prediction, and, particularly relevant for this study, a biocontrol agent obtained from Streptomyces bikiniensis has yet to be found. In this research, genomic analysis was used to predict the secondary metabolites of Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Positive traits such as the resistance of Streptomyces spores to environmental stresses can lead to the development of novel strategies for the organic control and precision agriculture of important plant diseases such as FHB, limiting the interventions in the field [35]. Field studies to verify the fitness and efficacy of the strain in farming conditions as well as genomic studies to decipher the potential mode of action and the molecules involved in the bacteria-plant interaction [36] are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Positive traits such as the resistance of Streptomyces spores to environmental stresses can lead to the development of novel strategies for the organic control and precision agriculture of important plant diseases such as FHB, limiting the interventions in the field [35]. Field studies to verify the fitness and efficacy of the strain in farming conditions as well as genomic studies to decipher the potential mode of action and the molecules involved in the bacteria-plant interaction [36] are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Gauze’s synthetic broth medium No. 1 [ 20 ] was used for strain HD-087 activation, DBY medium [ 19 ] was used for HD-087 fermentation for lipopeptide production, and PDB medium [ 21 ] was used for Guy11 culture.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have shown that S. bikiniensis HD-087 has antioxidant activity against cucumber Fusarium wilt and F. oxysporum [ 17 ], and its metabolites contain lipopeptide, which significantly inhibit the growth of M. oryzae mycelium and reduce the disease index of M. oryzae ([ 18 , 19 ]. To improve the production of lipopeptides in HD-087, in this study, the co-culture of M. oryzae Guy11 and S. bikiniensis HD-087 enhanced the production of lipopeptides and produced a new peptide compared to pure culture.…”
Section: Introductionmentioning
confidence: 99%
“…are crucial for their antifungal activities. Terpenes inhibit fungal growth (Adamczyk et al 2023 ) and pyrones interfere with spore germination and mycelial growth (Liu et al 2022a ; Degani and Gordan 2022 ). Others, such as gliotoxin and gliovirin, originally identified as antibiotic substances in some Trichoderma species, can induce oxidative stress and disrupt the intracellular redox homeostasis in fungal cells (Scharf et al 2016 ).…”
Section: Beneficial Traits Of Trichoderma Speciesmentioning
confidence: 99%